Determining entrepreneurs' characteristics towards psychological empowerment in Saudi Arabia - Mohammed A. Al Doghan; Mahmoud Mohamed Hussein Ali Alayis; Nadia Abdelhamid Abdelmegeed Abdelwahed, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
Human capital development and emancipation are recognized as the top priorities of not only Saudi Arabia's reforms and new plans but of all nations globally. However, most past research has concentrated on economic, social, and political empowerment, with little or no attention dedicated to psychological empowerment. Therefore, the purpose of this study was to examine, in the context of Saudi Arabia, the effect of the four entrepreneurial attributes of Self-esteem, Self-efficacy, Access to Information, and Job Autonomy on the Psychological Empowerment of the country's entrepreneurs. In this study, the researchers utilized the Meaning, Competence, Self-Determination, and Impact model of Spreitzer Psychological Empowerment. Using a web-based questionnaire issued with the assistance of Chambers of Commerce, the researchers gathered data from the Eastern Province governorates' entrepreneurs. The researchers used Structural Equation Modelling (SEM) to examine the data collected from 354 participants in this study. The findings indicate that Self-Esteem positively influences Meaning, Competence, Self-Determination, and Impact. Self-efficacy positively affects Psychological Empowerment (Meaning, Competence and Self- Determination). However, Self-Efficacy does not influence impact. In addition, Access to Information positively influences Psychological Empowerment to a limited extent (Impact). However, Meaning, Competence, and Self-Determination are unaffected. Job Autonomy has a favorable influence on Psychological Empowerment, Competence, Self-Determination, and impact to a limited extent. Nevertheless, Job Autonomy has little effect on meaning. The findings of this study advance the understanding of Psychological Empowerment's drivers and, in practice, aid policymakers in making informed decisions.